Shingles: Extensive Clinical Presentation of Herpes Zoster Infection (Bangladesh Journal of Otorhinolaryngology, 2020)
Shingles, also known as zoster, herpes zoster, or zona, is a viral disease characterized by painful skin rash with blisters.Typically the rash occurs on either side of face in a single stripe. Two to four days before the rash occurs there may be pain or tingling in the area. The rash usually heals within two to four weeks.Ongoing nerve pain may last for months or years,condition called postherpetic neuralgia. In those with poor immune function the rash may occur widely. If the rash involves the eye, vision loss may occur. Shingles is due to a reactivation of varicella zoster virus (VZV) within body. Chickenpox is due to an initial infection with VZV. Once chickenpox has resolved, the virus may remain inactive in nerve cells. Risk factors for reactivation include older age, poor immune function, and having had chickenpox before 18 months of age. Diagnosis is typically based on signs and symptoms. The shingles vaccine decreases the chance of shingles by about half in those between the ages of 50 and 80. It also decreases rates of postherpetic neuralgia. Antiviral medications such as aciclovir can reduce the severity and duration of disease if started within 72 hours of the appearance of the rash. NSAIDs or opioids may be used to help with the acute pain.It is estimated that about a third of people develop shingles at some point in their life. children may also get the disease. The number of new cases per year ranges from 1.2–3.4 per 1,000.Bangladesh J Otorhinolaryngol; October 2016; 22(2): 122-125